2016
DOI: 10.2147/ccide.s116353
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic treatment need among young Saudis attending public versus private dental practices in Riyadh

Abstract: ObjectiveTo assess and compare the severity of malocclusion and orthodontic treatment need among young Saudis receiving free treatment at public dental practices versus those paying for treatment at private practices.Materials and methodsThis retrospective study evaluated the records of 300 patients (179 females, 121 males; age 13–21 years) treated at orthodontic clinics from 2013 through 2015. The public sample was selected from orthodontic clinics at the College of Dentistry, King Saud University (KSU); the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 39 publications
0
14
1
Order By: Relevance
“…The IOTN is the most commonly used index, especially among epidemiological studies performed in the Middle East region. 2 According to the IOTN-DHC, this study showed that 24.3% of the cases had severe/extreme need for orthodontic treatment. Variable percentages have been reported by other studies performed in Arab countries.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…The IOTN is the most commonly used index, especially among epidemiological studies performed in the Middle East region. 2 According to the IOTN-DHC, this study showed that 24.3% of the cases had severe/extreme need for orthodontic treatment. Variable percentages have been reported by other studies performed in Arab countries.…”
Section: Discussionmentioning
confidence: 86%
“…1 The main reason for orthodontic treatment is enhancement of appearance from the patient’s point of view. 1 , 2 However, the need for orthodontic treatment is not influenced only by the patient’s perceptions; the orthodontist’s clinical examination is essential to support this perception and add greater awareness of the malocclusion situation. 2 , 3 Several indices were designed to classify malocclusion into groups in relation to the degree of treatment needed.…”
mentioning
confidence: 99%
See 3 more Smart Citations